ADVANTAGES AND DISADVANTAGES OF DISTANCE EDUCATION. LESSONS FROM THE COVID19 PANDEMIC - Rakhmatullaev, Marat (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The COVID19 pandemic has made changes not only in the health care, in our personal lives, but also in the education system especially. The purpose of the research is based on the analysis of the experience of universities of different countries, as well as a survey of teachers of Uzbekistan universities, that held classes during the quarantine, to identify the advantages and disadvantages of Distance Education(DE), as well as give recommendations for making decisions on development DE during the pandemic. To identify the advantages and disadvantages of distance learning during the COVID19 pandemic, an online survey was conducted among 126 university teachers. Respondents were asked to indicate the most important aspects of the advantages and problems of DE that they encountered during this period. Respondents indicated priorities - factors that had the greatest positive and negative impact on the learning process during the COVID19 pandemic. Analysis of this "short-term" period shows that DE has its pros and cons: Advantages: Saving time and money; Reducing the risk of getting sick; Development of DE technologies; Activating teachers to prepare e-courses; Equality of students to get knowledge. Disadvantages: Lack of direct contact with students; Complexity of individual work and in groups; "Presence Effect" of students; Activity of unscrupulous teachers; Complexity of knowledge assessment; Technological inequality among students; Decrease in the activity of scientific research.